Latin American thinking in science, technology and innovation: policies, determinants and practices - Paz Enrique, Luis Ernesto (2022)
In the theoretical order, there is a dispersion of published scientific literature on thought, trends and practice regarding science, technology and innovation in Latin America. The objectives of the study were: 1) to examine Latin American policies on science, technology and innovation and 2) to identify trends and patterns around the thinking, determinants and practices carried out for the development of science in Latin America. The study identifies the aspects that typify science and technology policies in Latin America, the eurocentric paradigms and the coloniality of knowledge. The Latin American initiatives for the emancipation of science are examined. It is concluded that the development of science, technology and innovation in Latin America have been fundamentally hand in hand with the state. Investments in science and technology in the Region have a greater incidence in the nations of Brazil, Mexico and Argentina and are mainly focused on the socalled hard sciences: technical and exact.